THE INFLUENCE OF ARABIC SOUND TOWARD ENGLISH PRONUNCIATION AT ENGLISH DEPARTMENT STUDENTS OF IAIN PALOPO - Yahya Amalia; Arifin Muliasari (Institut Agama Islam Negeri Palopo, 2015)
This thesis is aimed to find out the influence of Arabic sound toward English pronunciation especially English fricatives / f /, / ? /, and / ? /. The problem statement of this research is: Is there influence for people who master reading Quran in mastering English fricatives / f /, / ? /, and / ? / pronounciation in English Departement students of IAIN Palopo?The objective of this research is to find out the influence of person who masters produce Arabic sound based on makhraj huruf in mastering English fricative pronounciation in the third semester of English Departement students of IAIN Palopo. The research used descriptive qualitative. The subject of this research was 15 students who master produce Arabic sound based on makhraj huruf. The location was in IAIN Palopo. The instruments of this research were test reading task such as: words list reading task, sentences reading task, and passage reading task. and interview. The result of data analysis showed that if the participants have a good ability in pronuncing in Arabic sound they can pronunce English fricative pronunciation well. It means the people who masters reading Quran based on makhraj huruf can influence to master English pronunciation especially English fricatives / f /, / ? /, and / ? /. Suggestions: 1. To teachers or lecturers who teach pronunciation in IAIN Palopo to suggest to their students to more active reading holy Quran based on makhraj huruf because it can help them for mastering English Pronunciation especially English fricatives /f, ?, and ? /. 2. The researcher suggests for the next research to find out the same sounds in Arabic and English which are not found in this research because it is very helpful for the students to mastering English pronunciation.